2015
DOI: 10.1136/bmjopen-2015-008265
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family medicine clerkships in undergraduate medical education: a systematic review

Abstract: ObjectiveSynthesise evidence about the impact of family medicine/general practice (FM) clerkships on undergraduate medical students, teaching general/family practitioners (FPs) and/or their patients.Data sourcesMedline, ERIC, PsycINFO, EMBASE and Web of Knowledge searched from 21 November to 17 December 2013. Primary, empirical, quantitative or qualitative studies, since 1990, with abstracts included. No country restrictions. Full text languages: English, French, Spanish, German, Dutch or Italian.Review method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 75 publications
4
58
0
4
Order By: Relevance
“…This is obviously an area which needs further attention. Potentially, one of the ways this issue could be addressed is by including clinical placement opportunities earlier in the health degree programs [42] and including community health placements as a component of these earlier placements [43][44][45]. Another possible solution would be to pair students with patient volunteers from diverse backgrounds, who have serious or chronic medical conditions, an approach used in the Family Centre Experience [46].…”
Section: Discussionmentioning
confidence: 99%
“…This is obviously an area which needs further attention. Potentially, one of the ways this issue could be addressed is by including clinical placement opportunities earlier in the health degree programs [42] and including community health placements as a component of these earlier placements [43][44][45]. Another possible solution would be to pair students with patient volunteers from diverse backgrounds, who have serious or chronic medical conditions, an approach used in the Family Centre Experience [46].…”
Section: Discussionmentioning
confidence: 99%
“…Participating staff included physicians, nurses, dieticians, community health workers, medical assistants, and a scheduler. The team carefully considered the potential impact of the students on preceptors' efficiency in the primary care setting, as one systematic review found that although students improved job satisfaction, they negatively impacted preceptor workload and productivity (Turkeshi, Michels, Hendrickx, & Remmen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Currently ongoing international studies show that, in spite of positive educational benefits, even elaborately designed and realised curricular interventions have less influence upon the choice of medical specialty and the location of a practice than personal “practical experiences” [16], [17]. Accordingly, mentors are an indispensable part of similar projects [7], [8] and are particularly recommended for sitting in on lectures in the early phases of study, for which both students and mentors must however be prepared [6], [18], [19].…”
Section: Discussionmentioning
confidence: 99%